2010
DOI: 10.1016/j.ijsu.2009.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The pain of surgery: Pain experienced by surgeons while operating

Abstract: Many surgeons will experience pain while operating due to positioning or the instruments they use, however there are no guidelines from occupational health departments or training courses to help minimise these symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
132
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(143 citation statements)
references
References 4 publications
10
132
0
1
Order By: Relevance
“…In addition, the use of repetitive movements when operating instruments and tools may have a role in increased prevalence of upper limb tendinitis, especially of the elbow and the wrist. 13 Forst and colleagues 14 reported an increased prevalence (up to 3 times) of carpal tunnel syndrome in surgeons who frequently use a Kerrison rongeur. 14 In the study by Davis and colleagues 11 there was a higher prevalence of musculoskeletal disorders in surgeons who had been in practice for 20-30 years, whereas Auerbach and colleagues 12 found no such association.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of repetitive movements when operating instruments and tools may have a role in increased prevalence of upper limb tendinitis, especially of the elbow and the wrist. 13 Forst and colleagues 14 reported an increased prevalence (up to 3 times) of carpal tunnel syndrome in surgeons who frequently use a Kerrison rongeur. 14 In the study by Davis and colleagues 11 there was a higher prevalence of musculoskeletal disorders in surgeons who had been in practice for 20-30 years, whereas Auerbach and colleagues 12 found no such association.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] As a group, the surgeons subjectively noted less neck strain and fatigue using VITOM compared with traditional magnifying loupes alone; however, this finding is limited by lack of objective measures to better quantitate these potential differences. Based on previous studies using VITOM, we speculate that the decreased neck strain and fatigue is the result of improved ergonomics throughout the operations that enabled the surgeon to stand straight upright for hours in a comfortable position, thereby decreasing the need to lean or bend the neck to maintain magnifying loupe focus.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Although these magnifying instruments are essential to the optimal care of our patients, they often come at a detriment to the operating surgeon in the form of neck or back pain and fatigue. Furthermore, neck pain, back pain, and fatigue have been studied in multiple surgical disciplines, [6][7][8] but these factors, however, have not yet studied among pediatric surgeons. Drawbacks of traditional magnifying loupes include poor neck posture and frequent head movement to refocus the view, in addition to the inability to share the magnified visual field with surgical residents and assistants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Szeko et al, (2009) noted that the likelihood of musculoskeletal pain was closely related to the number of years worked in laparoscopic surgery [2]. In contrast, Sari et al (2010) found that musculoskeletal symptoms were more prevalent in surgeons with less experience [3], while Soueid et al (2010) found that such symptoms were often experienced at an early age [4]. Park et al (2010) however found no relationship between musculoskeletal symptoms and age [5].…”
Section: Introductionmentioning
confidence: 99%